2022
DOI: 10.1111/rda.14190
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin improves preserved semen quality at 17°C by enhancing sperm antioxidant and motility properties

Abstract: Porcine sperm is rich in polyunsaturated fatty acids; therefore, it is highly susceptible to oxidative damage during storage. Inhibition of oxidative stress during preservation is essential for maintaining sperm motility. Astaxanthin is a potent antioxidant used in the cosmetic and pharmaceutical industries. This study aimed to explore the effect of supplementing astaxanthin as an extender of porcine semen preservation dilutions at 17°C. Various concentrations of astaxanthin were added to diluted porcine semen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…When the accumulation of reactive oxygen molecules reaches a certain level, the antioxidant system of the sperm is disrupted, resulting in lipid peroxidation damage and subsequent irreversible negative effects on sperm vitality, viability, and quality [ 7 ]. Studies have shown that exogenous antioxidant substances can be added to semen diluents to reduce oxidative stress, limit the damage caused by ROS, extend sperm preservation time, and maintain quality after preservation [ 8 , 9 ]. Currently, the exogenous antioxidants used in semen preservation can be mainly divided into antioxidant enzymes, vitamins, amino acids, and plant extracts [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the accumulation of reactive oxygen molecules reaches a certain level, the antioxidant system of the sperm is disrupted, resulting in lipid peroxidation damage and subsequent irreversible negative effects on sperm vitality, viability, and quality [ 7 ]. Studies have shown that exogenous antioxidant substances can be added to semen diluents to reduce oxidative stress, limit the damage caused by ROS, extend sperm preservation time, and maintain quality after preservation [ 8 , 9 ]. Currently, the exogenous antioxidants used in semen preservation can be mainly divided into antioxidant enzymes, vitamins, amino acids, and plant extracts [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, mammalian spermatozoa are particularly sensitive to oxidative stress which result in collateral damage to sperm plasma membrane proteins and lipids (8). It is a proven fact that during storage and transport the impact of oxidative stress on the sperm cell increases (9).…”
Section: Introductionmentioning
confidence: 99%